2017
DOI: 10.1080/19420862.2017.1325556
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution mass spectrometry confirms the presence of a hydroxyproline (Hyp) post-translational modification in the GGGGP linker of an Fc-fusion protein

Abstract: Flexible and protease resistant (G4S) linkers are used extensively in protein engineering to connect various protein domains. Recently, several groups have observed xylose-based O-glycosylation at linker Ser residues that yield unwanted heterogeneity and may affect product quality. Because of this, an engineering effort was implemented to explore different linker sequence constructs. Here, we demonstrate the presence of an unexpected hydroxylation of a prolyl residue in the linker, made possible through the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…In addition to proteinogenic amino acids, non-proteinogenic amino acids and rare PTMs can also be detected in the protein sequence [ 19 21 ]. One of the more common mammalian non-proteinogenic amino acids is hydroxyproline, a known analog of proline that is found in collagen supporting its triple helix structure and stability [ 22 , 23 ]. Hydroxyproline is incorporated into collagen by post-translational modification [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to proteinogenic amino acids, non-proteinogenic amino acids and rare PTMs can also be detected in the protein sequence [ 19 21 ]. One of the more common mammalian non-proteinogenic amino acids is hydroxyproline, a known analog of proline that is found in collagen supporting its triple helix structure and stability [ 22 , 23 ]. Hydroxyproline is incorporated into collagen by post-translational modification [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxylation of proline occurs after protein synthesis and is catalyzed by the enzyme prolyl hydroxylase [ 25 ]. Tyshchuk et al [ 21 ] and Spahr et al [ 23 ] reported the presence of hydroxyproline and a corresponding hydroxylation site in recombinant therapeutics expressed using CHO expression systems. E .…”
Section: Introductionmentioning
confidence: 99%
“…35,45 Recently, hydroxyproline was reported at a similar high level (40%) in a partially rigid G 4 P linker as part of an Fcgrowth factor fusion protein stably expressed in CHO cells. 9 Also, the level of sTyr recently reported in the Lc CDR-1 of a CHO-derived antibody was determined to a relatively high (~20% at the peptide level, corresponding to~40% at intact level). 7 Together, these observations and the data presented here demonstrate that CHO cells are generally capable of introducing high levels of hydroxyproline and sulfotyrosine in therapeutic proteins, which thereby significantly increase the heterogeneity of the molecules.…”
Section: Discussionmentioning
confidence: 89%
“…6,7 Further uncommon enzyme-catalyzed PTMs (based on the experience and knowledge from IgGs and monoclonal antibodies (mAbs)) have been reported in non-IgG domains and linkers of antibody-fusion proteins. [8][9][10][11][12] In therapeutic proteins, PTMs are especially critical if they negatively influence drug potency or drug safety. Even if PTMs just increase the product heterogeneity of the desired molecules, when identified they need to be diminished or removed by manufacturing process optimizations or further protein engineering, or they at least have to be monitored and controlled to demonstrate batch consistency or comparability of manufactured clinical material.…”
Section: Introductionmentioning
confidence: 99%
“…An aspartate in the first EGF‐like module of these factors needs to be hydroxylated for Ca 2+ binding and to maintain its activity . Recently, hydroxylation of proline in the GGGGP linker of a Fc‐fusion protein and hydroxylation of lysine on the heavy chain Fab of an IgG1 were identified …”
Section: Introductionmentioning
confidence: 99%